Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share terhadap Kemampuan Komunikasi Matematika Siswa Kelas VIII SMPN 21 Mataram Tahun Ajaran 2021/2022 - Junaidi; Amrullah; Nurhadiatun Nufus; Nyoman Sridana (Jurnal Riset Pendidikan Matematika Jakarta, 2022)
This study aims to determine the effect of implementing the Think Pair Share cooperative learning model on the mathematical communication skills of eighth grade students of SMP Negeri 21 Mataram in the 2021/2022 academic year. This type of research is a quasi-experimental study with a posttest only nonequivalent control group design. The population in this study were all grade VIII students of SMP Negeri 21 Mataram in the academic year 2021/2022. The samples in this study were grade VIII A and VIII B students who were taken using a cluster random sampling technique. Class VIII A as the experimental class by applying the Think Pair Share type of cooperative learning model while class VIII B as the control class by applying the direct learning model. The instrument used in this study was an observation sheet to see the implementation of the learning model used and a test question in the form of a description of 3 questions to see students' mathematical communication skills. The data analysis technique used is t-test. Based on the results of data analysis, the value of tcount> ttable so that the average post-test results of the experimental class students' mathematical communication skills were better than the average post-test results of the control class's mathematical communication skills, this means that h0 where there is an effect of implementing the cooperative learning model type Think Pair Share on the mathematical communication skills of class VIII SMP Negeri 21 Mataram in the academic year 2021/2022.